Description of the tadpole of Proceratophrys carranca Godinho, Moura, Lacerda and Feio, 2013, (Anura, Odontophrynidae) - Peixoto, Marco Antônio Amorim; Pires, Daniellen Martins Vieira; Godinho, Leandro Braga; Feio, Renato Neves (Zootaxa, 2014)
Proceratophrys carranca Godinho, Moura, Lacerda & Feio, 2013 belongs to the P. cristiceps group, which currently contains 15 species (Brandão et al. 2013). This group is defined by species lacking palpebral appendages, postocular swellings and inhabiting mainly seasonally dry open environments (Cerrado and Caatinga domains) in Brazil (Giaretta et al. 2000). Using molecular data, Amaro et al. (2009) showed the non-monophyletic status of the P. cristiceps group. These authors emphasize that more studies are needed for to understand the taxonomy of the genus Proceratophrys. Larval characters are important tools that make a significant contribution to the resolution of taxonomic problems.